Globalization Strategies and Firm Competitiveness in Rwanda - Ndagano, David (Journal of Strategic Management, 2024)
Purpose: The aim of the study was to assess the globalization strategies and firm competitiveness in Rwanda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that companies leveraging globalization can tap into new markets, diversify their product offerings, and optimize their supply chains, leading to enhanced competitive positioning. By adopting strategies such as international expansion, strategic alliances, and leveraging global talent, firms can achieve economies of scale and scope, reduce costs, and increase innovation through exposure to diverse markets and ideas. However, successful globalization requires navigating challenges such as cultural differences, regulatory compliance, and political risks. Firms that effectively implement globalization strategies often see improved market share, profitability, and long-term sustainability, positioning themselves favorably against competitors who may not capitalize on these global opportunities. Implications to Theory, Practice and Policy: Porter's diamond model, resource-based view and transaction cost economics may be used to anchor future studies on assessing the globalization strategies and firm competitiveness in Rwanda. Encourage firms to adopt a dynamic approach to globalization strategies by continually assessing market conditions, competitive landscapes, and customer preferences. Advocate for policies that support cross-border trade, investment, and collaboration while addressing regulatory challenges and trade barriers that hinder firms' global expansion efforts.